Role of regional anesthesia in minimizing opioid use and enhancing patient recovery: a case series - Irwan Setiadi; Muhammad Rezanda Alifahna; Radian Ahmad Halimi; Dewi Yulianti Bisri (Journal of Medical Case Reports)
Abstract Background Enhanced Recovery After Surgery employs evidence-based strategies to improve outcomes across the preoperative, intraoperative, and postoperative phases. In spinal surgery, compared with traditional management with general anesthesia, regional anesthesia offers benefits such as reduced pain, improved organ function, faster mobility, and shorter hospital stays. Studies have shown that regional anesthesia, particularly spinal anesthesia, results in shorter operation times, lower postoperative pain, and fewer thrombosis complications than does general anesthesia. The implementation of regional anesthesia in Enhanced Recovery After Surgery protocols for elective spinal surgeries aims to minimize hospital stays and opioid use, significantly enhancing recovery and patient outcomes. Patient presentation Two Sundanese patients underwent laminectomy surgery for chronic low back pain and disc degeneration. The first, a 57-year-old man, presented with bulging discs and osteophytes in the lumbar spine and underwent a 2-hour surgery in the prone position. His vital signs remained stable throughout. The second patient, a 54-year-old woman, also had similar lumbar spine issues and underwent equally successful surgery under stable hemodynamic conditions. Conclusion Regional anesthesia during lumbar spine surgery ensures stable perioperative hemodynamics and reduces opioid needs, which aligns with Enhanced Recovery After Surgery principles, promoting faster recovery and better outcomes.